Pretreatment with standard‐dose intravenous methylprednisolone does not improve outcomes in newly diagnosed immune thrombocytopenia (ITP). (12th March 2018) - Essilini, Anaïs; Comont, Thibault; Germain, Johanne; Brun, Natacha; Dingremont, Claire; Castel, Brice; Arista, Sophie; Madaule, Serge; Sailler, Laurent; Lapeyre‐Mestre, Maryse; Beyne‐Rauzy, Odile; Godeau, Bertrand; et al.
Abstract: Objective: To assess the benefits and harms to initiate corticosteroids with intravenous methylprednisolone at a conventional dose (1 mg/kg/d) to treat adults with immune thrombocytopenia (ITP). Methods: Population stemmed from the prospective multicenter CARMEN registry and included newly diagnosed hospitalized ITP adults with platelet counts<30 × 10 9 /L. We compared the patients treated with conventional‐dose methylprednisolone (CDMP) before continuing with oral prednisone to patients treated with just conventional‐dose oral prednisone (CDOP). The primary outcome was the time until response. Secondary outcomes were time until complete response, response rate, complete response rate, duration of hospital stay, and occurrence of adverse drug reactions. Analyzes were adjusted for propensity score and for exposure to intravenous immunoglobulin. Results: Among the included 87 patients, the median time to response was 3 days in the CDMP group vs 4 in the CDOP group (adjusted hazard ratio [aHR]: 1.35; 95%CI: 0.76‐2.41). The CDMP group had an earlier complete response (aHR: 2.29; 95%CI: 1.20‐4.36). There was no difference between the groups regarding other secondary outcomes. Conclusions: Initiating methylprednisolone at a conventional dose provided no significant benefit compared to giving oral prednisone only to adults with ITP.